Hypertyroidism and thyroid carcinoma - Perrone, Luis; Paperán, Juan; Estrugo, Roberto; Bercianos, Carlos; Maggiolo, Jorge (Cirugía del Uruguay, 1978)
Two cases o·f Thyroid carcinoma in patients with hypertyroidism. A brief review of the literature is done. In both cases carcinoma were found in the pathologic study of the resected thyroids. The patients· are free of tumor 4 and 5 years after surgery.